2020
DOI: 10.3390/laws9010006
|View full text |Cite
|
Sign up to set email alerts
|

Public Interest, Health Research and Data Protection Law: Establishing a Legitimate Trade-Off between Individual Control and Research Access to Health Data

Abstract: The United Kingdom's Data Protection Act 2018 introduces a new public interest test applicable to the research processing of personal health data. The need for interpretation and application of this new safeguard creates a further opportunity to craft a health data governance landscape deserving of public trust and confidence. At the minimum, to constitute a positive contribution, the new test must be capable of distinguishing between instances of health research that are in the public interest, from those tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Ultimately, what drives shifts and re-designs to a decision-making process is the need to maintain qualities 'that provide arguments for the acceptability of its decisions' (Mashaw, 1983, p. 24; see also Taylor & Whitton, 2020). This may be a political decision but it is not just the backdrop to the Health Service (Control of Patient Information) Regulations 2002 that suggests that the social legitimacy of the public use of health data should not be taken for granted.…”
Section: Legislative Purpose and (Social) Legitimacymentioning
confidence: 99%
“…Ultimately, what drives shifts and re-designs to a decision-making process is the need to maintain qualities 'that provide arguments for the acceptability of its decisions' (Mashaw, 1983, p. 24; see also Taylor & Whitton, 2020). This may be a political decision but it is not just the backdrop to the Health Service (Control of Patient Information) Regulations 2002 that suggests that the social legitimacy of the public use of health data should not be taken for granted.…”
Section: Legislative Purpose and (Social) Legitimacymentioning
confidence: 99%
“…On the one hand, like different health problems in ancient times, millions of Australians are currently despairing at this data breach war and they are worried about their privacy and health information, which might be sold and used by unauthorized third-parties, while on the other hand, it is necessary to disclose and give permission of their medical information to different health-related professionals towards a better treatment. There is still no clear guidance of the secondary use of health data where that is "in the public interest" [126].…”
Section: Safeguarding Health Records Against Data Breachesmentioning
confidence: 99%
“…For example, in a qualitative study investigating perceived barriers among GPs towards recruiting patients into RCTs lack of confidence in introducing research participation requests to their patients was found as one main reason [19]. Data protection regulations also make it particularly difficult to contact patients directly [33]. Particularly in studies with a limited funding period, extending periods of recruitment represent a major problem [34].…”
Section: Introductionmentioning
confidence: 99%